Cost-effectiveness analysis of empiric antibiotics in hospitalized community-acquired Pneumonia - Yeni Farida; Qisty Aulia Khoiry; Muchtar Hanafi; Maryani Maryani (Pharmaciana, 2022)
Community-Acquired Pneumonia (CAP) remains an important infectious disease due to its impact on patient outcomes. Â This study aimed to investigate the clinical outcome and especially costs of hospitalization for community-acquired pneumonia (CAP) concerning empirical antibiotics. This research was conducted to estimate the cost-effectiveness of levofloxacin, ceftriaxone, and a combination of ceftriaxone and azithromycin aiming to improve the clinical outcome of CAP. A retrospective observational study was conducted in secondary care, University Hospital in Surakarta, Central Java, Indonesia. The study enrolled all CAP patients hospitalized in the period January until December 2018, with agesâ‰¥ 18 years old, and at least used antibiotic for three days. We compared cost-effectiveness, as measured by total cost and proportion of patients successfully treated, of 3 empirical antibiotics for inpatient CAP, involving ceftriaxone, levofloxacin, or combination ceftriaxone + azithromycin. Our analyses were conducted based on a healthcare perspective. In all groups were analyzed based on severity classification (Pneumonia Severity Index score). The use of levofloxacin instead of ceftriaxone improved clinical response, but it is more expensive. Levofloxacin was the most cost-effective based on ACER value. Treatment using a combination of ceftriaxone + azithromycin was more expensive without added benefit. Based on this study, the use of levofloxacin as the first-line therapy for CAP could be maintained because it was more cost-effective than other alternatives. Since the limitations, a study on a broader population is needed to confirm these findings.